(untitled) (Indian Journal of Animal Production and Management, 2014)
Effects of Inbreeding, sire, period and season on age at first calving (AFC) and its phenotypic and genetic association with other reproductive traits viz., first service period (FSP) and first calving interval (FCI) were studied on 191 Gir cows maintained at the Kasturba Gandhi National Memorial Trust Dairy Farm, Kasturbagram, Indore (M.P.). The AFC in these cows averaged 1787.46±36.11 days and was significantly (p<0.01) affected by inbreeding. The effects due to sire, period and season were non- significant. The heritability estimate of AFC was low (0.09±0.12) with large standard error. The phenotypic correlations of AFC with FSP and FCI were both positive and significant (p<0.01). It was concluded that inbreeding had deteriorating effect on the age at first calving and hence to improve the age at first calving in this herd avoidance of inbreeding along with ameliorative managerial practices should be adopted.